MEMAHAMI FATWA MAJELIS ULAMA INDONESIA TENTANG PEMANFAATAN ZAKAT, INFAK, DAN SHADAQAH UNTUK KORBAN COVID-19 DALAM PENDEKATAN HUKUM ISLAM KONTEMPORER - Dwi Novaria Misdawati; Athoillah Islamy (Institut agama islam negeri Padangsidimpuan, 2022)
Economic problems as a result of the Covid-19 pandemic in Indonesia have prompted serious handling by all elements of society, especially the government. Responding to this problem, the Indonesian Ulema Council (MUI) was present through the MUI fatwa No. 23 of 2020 concerning the Utilization of Zakat, Infaq, and Sadaqah Assets to cope with the pandemic and its implications. This study intends to identify the model of the contemporary Islamic legal approach used in the formulation of the fatwa. This literature study uses a philosophical normative approach. The theory that becomes the theory of analysis is the Islamic legal system approach offered by Jasser Auda. This study shows the formulation of the MUI fatwa No.23 of 2020 using an integrative Islamic law approach. This is based on the characteristics contained in the various elements in the formulation of the fatwa. First, the comprehensive and multidimensional character, namely using various textual arguments that are universal ('aam). Second, the character of intent, namely using the arguments of various rules of Islamic law that focus on benefit. Third, the cognitive character, which uses various classical Islamic legal thoughts, but does not become an independent argument, but is combined with other perspectives that are part of the basis for formulating a fatwa.